2001
DOI: 10.1046/j.1365-2052.2001.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship amongst the major non‐coding regions of mitochondrial DNAs in wild boars and several breeds of domesticated pigs

Abstract: We completed phylogenetic analysis of the major non-coding region of the mitochondrial DNA (mtDNA) from 159 animals of eight Euro-American and six East Asian domesticated pig breeds and 164 Japanese and five European wild boars. A total of 62 mtDNA haplotypes were detected. Alignment of these regions revealed nucleotide variations (including gaps) at 73 positions, including 58 sites with transition nucleotide substitutions, and two transversion substitutions. Phylogenetic analysis of the sequences could not or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 17 publications
6
61
0
1
Order By: Relevance
“…The prevalence of cytB and D-loop European and Asian haplotypes had been previously studied in major European commercial breeds such as the Large White, Landrace, Duroc, Hampshire and others [2,7,10]. These studies demonstrate that most of these standard breeds had been extensively introgressed with Asian alleles.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The prevalence of cytB and D-loop European and Asian haplotypes had been previously studied in major European commercial breeds such as the Large White, Landrace, Duroc, Hampshire and others [2,7,10]. These studies demonstrate that most of these standard breeds had been extensively introgressed with Asian alleles.…”
Section: Resultsmentioning
confidence: 69%
“…Phylogenetic analysis of the porcine mitochondrial genome has revealed that Wild Boar subspecies were independently and simultaneously domesticated in Asia and Europe 9000 YBP [2,[6][7][8]10]. Major European and Asian mtDNA clades diverged well before this domestication event and the estimates for the time of divergence range from 58 000 to 900 000 YBP [1,2,6,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the Large White present in line B, which is a hyperprolific breed with a higher content of fat in the carcass, may also have influenced this characteristic of line B. According to Watanabe et al (1986), Giuffra et al (2000) and Okumura et al (2001), the Large White breed was influenced by Chinese breeds at the end of the 18th century. Besides, molecular biology studies in Large White breed clearly show an introgression of Asian breeds into European breeds, by the high proportion of mitochondrial DNA originating from Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Haplotypes of the 574-bp mtDNA were used in neighbor-joining analysis [12], which was performed using the PHYLIP program package, version 3.572 [3]. Sixty-three previously reported haplotypes (accession nos: D42170-D42174, D42178-D42185, AB015087-AB015086, AB041465-AB041473, AB041474-AB041476, AB041479-AB041485, AB041487-AB041493, AB041495-AB041499, AB053623-AB053627, D42176, AB071706, AB071707 and AB055222) [6,10,11,14,15] were used as reference sequences in NJ analysis.…”
mentioning
confidence: 99%